Islamic Education and Global Citizenship in Character Development - Wahab, Gusnarib A. (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Education holds a strategic role in developing student character, aiming for individuals who are morally upright, knowledgeable, and socially conscious. In the context of globalization, marked by technological advancement and open information, Islamic education must synergize with Global Citizenship (GC) values to cultivate a generation that is not only intellectually astute but also concerned with humanitarian issues and moral responsibility as world citizens. This study analyzes the role of integrating Islamic education and GC in student character formation. Using a qualitative library research approach, relevant literature—including books, academic journals, and policy documents—was analyzed. The findings indicate that core Islamic values, such such as faith, honesty, justice, and compassion, align strongly with GC principles like tolerance, social justice, responsibility, and peace. This synergy can be actualized through integrated curricula, values-based learning, and teacher role-modeling in daily educational practice. Character formation rooted in Islamic values yet open to global diversity will produce a generation that is virtuous (akhlakul karimah), critical, adaptive, and capable of contributing positively both locally and internationally. Therefore, Islamic education and global citizenship are not conflicting but complementary forces in shaping holistic and competitive student character in the global era.